The strength of e-WOM and product quality on purchase decisions in café smile and sandwich in Palangka Raya City - Peridawaty Peridawaty; Achmad Syamsudin (Institute of Computer Science (IOCS), 2023)
Research in the field of marketing in improving purchasing decisions at Smile and Sandwich cafes. Problems in the cafe business require active business actors to survive in uncertain business conditions, with expertise in increasing income and being able to meet consumer needs with the power of reviews from social media or the power of e-WOM. Besides that, the importance of the role of quality products to improve purchasing decisions. The research was conducted quantitatively with SPSS 22.0, on 50 cafe customer respondents. The research results prove the significance of the indicators for each variable and there is a good relationship of 58% in increasing purchasing decisions. Implications of the results for improving purchasing decisions with technology-based e-WOM and the importance of delivering quality products to consumers. Future research can test the mediation of product innovation.